2021
DOI: 10.33448/rsd-v10i3.13038
|View full text |Cite
|
Sign up to set email alerts
|

Anatomopathological and immunohistochemical findings of natural Brucella abortus infection in buffalo uterin and peri-vaginal lymph nodes

Abstract: The present work aimed to evaluate the macro and microscopic lesions and the distribution of Brucella sp. in the reproductive tract of seropositive female buffaloes to brucellosis. Nineteen genital tracts and eighteen peri-vaginal lymph nodes from previous serum reagent animals to brucella were collected from slaughterhouse, processed and submitted to Fisher's exact test (5%). It was not observed uterine macroscopic lesions from non-pregnant and pregnant until the four month, as well as are infrequent in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The histopathological changes were examined in the uterine tissue of infected ewes, and these changes agreed with the histological changes observed by (Ayala et al, 2021) who found the mononuclear inflammatory cells infiltration and aggregation in uterine tissues, along with sites of fibrosis and calcification. a prominent mononuclear cells infiltrate and macrophages surrounded a small focus of calcification in the compact layer of the endometrium.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 82%
“…The histopathological changes were examined in the uterine tissue of infected ewes, and these changes agreed with the histological changes observed by (Ayala et al, 2021) who found the mononuclear inflammatory cells infiltration and aggregation in uterine tissues, along with sites of fibrosis and calcification. a prominent mononuclear cells infiltrate and macrophages surrounded a small focus of calcification in the compact layer of the endometrium.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 82%